TPACK: Teachers' Needs - Aryuliva Adnan; Caca Yunisari (Ta'dib, 2023)
The advancement of technology develops a new framework in the education field, known as TPACK. It integrates the theory of pedagogy, content, and technology. Using mix method (qualitative-quantitative) research design, the researchersÔÇÖ goal was to know the implementation of TPACK in designing lesson plans by English teachers. Furthermore, the researchers decided to use purposive sampling for each education level (junior, senior, and vocational schools) in West Sumatera. To gain the data, the researchers conducted document analysis, observation, questionnaires, and interviews. After analyzing the data, it was found that the teachers in terms of preparing the lesson, the result showed teachersÔÇÖ pedagogical competence was higher than technological and content knowledge because they adopted lesson plans from the internet. However, regarding the competent of teachers in teaching and learning process, it seemed that they were more competent in technology compared with pedagogy and content knowledge because novice teachers were more familiar in using technology compared to experienced teachers. Surprisingly, in terms of assessment, the teachers were more competent in pedagogy compared with technology and content knowledge. However, content knowledge were not illustrate significantly since they could not understand and develop learning material based on studentsÔÇÖ needs. In conclusion, teachersÔÇÖ competence with TPACK were still below average in terms of┬á understanding the concept, implementation, and assessment, so that they need workshop and seminar to improve their teaching quality and TPACK understanding and implementation.